Vacationing in Hawaii with Resendez Family - Watkins, Howard::::::::: (1987)
Howard Watkins ??. Caroline Resendez, ?, Rose O'Reilly, Albert Watkins, Joey Resendez, Nellie and Inder Resendez arriving at airport